Regulation of mouse exploratory behaviour by irradiance and cone-opponent signals - E. Tamayo; J. W. Mouland; R. J. Lucas; T. M. Brown (BMC Biology, 2023)
Abstract Background Animal survival depends on the ability to adjust behaviour according to environmental conditions. The circadian system plays a key role in this capability, with diel changes in the quantity (irradiance) and spectral content (‘colour’) of ambient illumination providing signals of time-of-day that regulate the timing of rest and activity. Light also exerts much more immediate effects on behaviour, however, that are equally important in shaping daily activity patterns. Hence, nocturnal mammals will actively avoid light and dramatically reduce their activity when light cannot be avoided. The sensory mechanisms underlying these acute effects of light are incompletely understood, particularly the importance of colour. Results To define sensory mechanisms controlling mouse behaviour, we used photoreceptor-isolating stimuli and mice with altered cone spectral sensitivity (Opn1mwR), lacking melanopsin (Opn1mwR; Opn4 −/− ) or cone phototransduction (Cnga3 −/− ) in assays of light-avoidance and activity suppression. In addition to roles for melanopsin-dependent irradiance signals, we find a major influence of spectral content in both cases. Hence, remarkably, selective increases in S-cone irradiance (producing a blue-shift in spectrum replicating twilight) drive light-seeking behaviour and promote activity. These effects are opposed by signals from longer-wavelength sensitive cones, indicating a true spectrally-opponent mechanism. Using c-Fos-mapping and multielectrode electrophysiology, we further show these effects are associated with a selective cone-opponent modulation of neural activity in the key brain site implicated in acute effects of light on behaviour, the subparaventricular zone. Conclusions Collectively, these data reveal a mechanism whereby blue-shifts in the spectrum of environmental illumination, such as during twilight, promote mouse exploratory behaviour.